1999
DOI: 10.1089/088922299309676
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Virologic Failure of Antiretroviral Triple-Drug Therapy in a Community-Based Cohort

Abstract: Highly active antiretroviral therapy fails to reach its recommended goal of sustained suppression of viral replication in a substantial proportion of patients. We analyzed incidence and predictors of virologic failure of the first regimen of a triple-drug combination therapy, including a protease inhibitor and two nucleoside analog reverse transcriptase inhibitors (NRTIs), in 274 HIV-infected patients. Long-term virologic response to combination therapy including salvage regimens was assessed 2.5 years after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…26 Comparison of HIV-1 RNA levels from the different compartments revealed that virological response in plasma mirrored response in PBMC with rem arkable accuracy. The rational for having defined virological response in our patients by the ratio of baseline and nadir HIV-1 RNA levels 13 was based on observation s that found "high baseline" [27][28][29] and "high nadir levels" 3 0,31 of plasma virem ia to be predictors for virological failure of antiretrovir al therapy. Reminiscent of the correlation of virological responses, PBMC HIV-1 RNA levels were also directly correlated with viral RNA levels in plasma at baseline and throughout the whole observation period.…”
Section: O M B In a Tio N A N Tire Tr O V Ira L D R U G Th E Ra Py mentioning
confidence: 99%
“…26 Comparison of HIV-1 RNA levels from the different compartments revealed that virological response in plasma mirrored response in PBMC with rem arkable accuracy. The rational for having defined virological response in our patients by the ratio of baseline and nadir HIV-1 RNA levels 13 was based on observation s that found "high baseline" [27][28][29] and "high nadir levels" 3 0,31 of plasma virem ia to be predictors for virological failure of antiretrovir al therapy. Reminiscent of the correlation of virological responses, PBMC HIV-1 RNA levels were also directly correlated with viral RNA levels in plasma at baseline and throughout the whole observation period.…”
Section: O M B In a Tio N A N Tire Tr O V Ira L D R U G Th E Ra Py mentioning
confidence: 99%
“…In a cohort of Swiss HIV patients, lapses in adherence preceded more than half of all therapy failures. (Paris et al, 1999) Because the adherence reductions induced by alcohol consumption may decrease survival, it is possible that HIV clinical guidelines should place a greater emphasis on screening for alcohol use disorders and facilitating access to alcohol cessation interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This proportion has increased in recent years [11][12][13]; however, viral replication is still not fully controlled in all patients at all times. Previous analyses have found that a patient is most likely to fail in the first few months after initial viral suppression [14], that increasing time with viral suppression decreases the risk of rebound [15,16], and that treatment interruptions with detectable viral load [17] increase the risk of rebound, as does pre-cART exposure to nucleoside reverse transcriptase inhibitor (NRTI) regimens [15,18]. Additionally, low CD4 cell counts, high viral load, a slow virological response to cART and prior AIDS diagnosis were linked to lack of durable viral load undetectability [19,20].…”
mentioning
confidence: 99%